The Fear of Imperfection: Career Anxiety as an Impact of Body Dysmorphic Disorder - Merri Hafni; Yuliana Yuliana; Laelatul Anisah; Rosa Dovita; Risma Kumara Rani; Ainul Husna; Lira Erwinda (Bulletin of Counseling and Psychotherapy, 2025)
Body Dysmorphic Disorder (BDD) causes individuals to focus excessively on physical flaws, thus reducing self-confidence and belief in their abilities. This low self-confidence can trigger career anxiety, as individuals feel their appearance is a barrier to competing and adapting in the workplace. However, since evidence on the relationship between BDD and career-related psychological outcomes among students remains fragmented, little is known about how body image concerns specifically influence students’ readiness and confidence in pursuing their future careers. This study aims to determine the effect of BDD on the level of career anxiety of students. The method used is quantitative correlation. The research sample was 310 randomly selected students. Data analysis in this study used simple linear regression. The results showed a significant influence between BDD and career anxiety. The higher the level of BDD, the higher the career anxiety experienced by students. New findings from this study reveal that social media factors, social pressure, and family expectations can exacerbate the impact of BDD on students' career readiness. The implications of this study emphasize the importance of Guidance and Counseling services in addressing students' body image issues and career anxiety holistically and preventatively.